Impact of Tourism on Indian Economy - Simon, Simeon S. (SFIMAR Research Review, 2020)
The travel and tourism industry in India has an enormous potential to influence Indian economy. Tourism has always been a significant contributor to employment generation and a huge source of foreign exchange earnings for any country. The tourism sector not only employs people in Metros but also provides livelihood to people across all social strata in rural areas. Hence, the pursuit of this research work is to gain a deeper understanding on the impact of tourism on the Indian Economy in the emerging scenario. Indeed, travel and tourism has been significantly impacting Indian economy in an integrative manner. This paper identifies several contributors influencing economic growth and the role of tourism in GDP, and inflow of foreign tourists versus domestic visitors. An extensive literature review has been done on concepts related to tourism including review of research papers and articles related to tourism and its effects on the economy. This research has been conducted by a secondary data method. The objective of this research is to study and understand the opportunities of tourism in India, several Government initiatives taken towards development of the tourism sector and to get deeper insight on impact of tourism on the economy of India.